Diversity of Flora in A Pulpwood Plantation of Sumatran Elephant Elephas maximus sumatranus Habitat in Air Sugihan Wetlands, Ogan Komering Ilir, South Sumatra - PRAGUSTIANDI, GUNTUR; APRILLIA, INA; SETIAWAN, ARUM; YUSTIAN, INDRA (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2024)
Knowledge about flora biodiversity is an important component to determine the best strategy for policy makers in making decisions. A study on flora diversity with assesment on Sumatran Elephant habitats has been conducted in PT. Bumi Andalas Permai (PT. BAP). This area is a home range for Sumatran Elephant habitat in Sumatra. This research is to obtain basic information before carrying out other activities that might influence the composition of vegetation in the future. Determining the sampling location uses a purposive method, collecting data using observation plots which are expected to represent each existing vegetation type. Based on research conducted, there is only one species of plant at tree level, one species at pole level, and two species at sapling level, and 32 species at seedling level. Species diversity at the tree, pole and sapling level in study site. The species diversity in PT. BAP is included in low level category, under criteria H'=0, H'=0 and H'=0.69 respectively. Meanwhile, for the seedling/undergrowth level, H'= 3.05. There are very few species of plants at the level of trees, poles and stakes because the land is an open area in the form of bushes, thickets, swamps and rice fields on the side of an artificial canal.